2011
DOI: 10.1038/ijo.2011.146
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hormones, energy balance and bariatric surgery

Abstract: Despite increasing understanding of the changes in gastrointestinal and central neuroendocrine signaling following gastric bypass surgery (GBP) in morbidly obese patients, the mechanisms underlying weight loss and weight loss maintenance are not completely understood. Changes in energy expenditure are increasingly recognized as an important factor contributing to weight loss and metabolic effects in patients following GBP surgery. Experimental data regarding changes in energy balance following metabolic surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 56 publications
0
21
0
3
Order By: Relevance
“…Following RYGB, patients typically lose approximately 30% of total body weight or 60–70% of excess body weight [3]. Although the exact mechanism remains unknown, it is believed that factors other than restriction and malabsorbtion of the ingested food may contribute to the beneficial effects of RYGB surgery [4], [5]. Following RYGB, patients voluntarily restrict consumption of calorie-dense, highly palatable foods such as fats, concentrated carbohydrates, ice cream, and sweetened beverages [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Following RYGB, patients typically lose approximately 30% of total body weight or 60–70% of excess body weight [3]. Although the exact mechanism remains unknown, it is believed that factors other than restriction and malabsorbtion of the ingested food may contribute to the beneficial effects of RYGB surgery [4], [5]. Following RYGB, patients voluntarily restrict consumption of calorie-dense, highly palatable foods such as fats, concentrated carbohydrates, ice cream, and sweetened beverages [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The increased resting energy expenditure in the animal models after GB is in accordance with some, but not all, reports in humans. The discrepancies in the clinical studies may include the heterogeneity of patient populations and measurements of energy expenditure for a limited time using portable metabolic carts under artificial rather than “free-living” conditions [35]. Nerveless, resting energy expenditure has been suggested to be a therapeutic target for obesity [32], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic caloric deprivation is normally accompanied by a decrease in resting energy expenditure as the body strives to conserve energy [ 42 ]. These are some inconsistencies as to what happens to resting energy expenditure after bariatric surgery, but the majority of human and/or animal studies have shown that it remains stable on decreases after RYGB, VSG and AGB [ 21 , 43 -52 ].…”
Section: Energy Expenditurementioning
confidence: 99%